2020
DOI: 10.1093/pcp/pcaa077
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Physiological Alterations in Chickpea under Elevated CO2 Concentrations

Abstract: The present study reports profiling of the elevated CO2 concentration responsive global transcriptome in chickpea along with a combinatorial approach for exploring interlinks of physiological and transcriptional changes, important for the climate change scenario. Various physiological parameters were recorded from chickpea cultivars (JG 11 and KAK 2) raised in OTC (Open-Top-Chamber) under ambient (380 ppm) and two stressed/elevated CO2 concentrations (550 ppm and 700 ppm) under different stages of plant growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…The secondary metabolism category was considerably down-regulated in sorghum GPR under water-deficit and high [CO 2 ] conditions, with 148 DEGs repressed, approximately 8% of the total number of genes regulated (Table S3). It is already well known that E[CO 2 ] and drought also induce the production of secondary metabolites (Palit et al, 2020b; Palit et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…The secondary metabolism category was considerably down-regulated in sorghum GPR under water-deficit and high [CO 2 ] conditions, with 148 DEGs repressed, approximately 8% of the total number of genes regulated (Table S3). It is already well known that E[CO 2 ] and drought also induce the production of secondary metabolites (Palit et al, 2020b; Palit et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…In legumes, for example, hybrid comprehensive assemblies were generated in the case of pigeonpea (Kudapa et al., 2012) and chickpea (Kudapa et al., 2014) by analyzing sequencing data from three different platforms (Sanger, FLX/454, and Illumina). In a different study, transcriptome analysis under elevated CO 2 concentrations identified stress responsive candidate genes and pathways mainly involved in sugar and starch metabolism, chlorophyll, and secondary metabolites biosynthesis (Palit et al., 2020a). Gene expression profiling data from developed transcriptome assemblies enabled identification of candidate genes associated with different traits of interest and stress response.…”
Section: Rapidly Evolving Omics Approachesmentioning
confidence: 99%
“…Measuring transcriptome dynamics is a comprehensive method for assessing environmental responses and their alteration due to genetic, developmental and physiological factors ( Han et al. 2020 , Palit et al. 2020 , Ye et al.…”
Section: Introductionmentioning
confidence: 99%